Enhancing the Physico-Mechanical Properties of Concrete via Hydrochloric Acid Treatment on Palm Oil Fuel Ash Additives - Shukor, Siti Nurain; Noh, Mohamad Zaky (Enhanced Knowledge in Sciences and Technology, 2025)
Concrete faces significant sustainability challenges due to its reliance on ordinary Portland cement (OPC), which contributes to high CO₂ emissions and environmental degradation. Drying and heat contraction can cause conventional concrete to shrink and crack early in its life. This study explores the use of chemically treated palm oil fuel ash (POFA) as a sustainable alternative to OPC, presenting a novel approach to enhancing the physico-mechanical properties of concrete while addressing environmental concerns. The POFA underwent grinding, sieving, heat treatment at 1000°C, and acid treatment with 2M HCl before being incorporated into concrete samples at replacement levels of 0%, 10%, 20%, and 30%. After curing for seven and twenty-eight days, the samples were evaluated for density, porosity, compressive strength, and water absorption. The sample with 20% POFA replacement demonstrated the most significant improvements, achieving an optimal density of 2.172 g/cm³, the lowest water absorption (0.84%), smallest porosity (1.78%), and optimal compressive strength (1097.00 MPa). These enhancements are attributed to improved pozzolanic reactions, which densified the concrete matrix by reducing voids. While the study highlights the potential of POFA in sustainable construction, limitations such as the availability and processing cost of POFA warrant further investigation. Future research should explore the long-term durability of POFA concrete and its performance under varying environmental conditions, paving the way for its broader application in eco-friendly building practices.